Criteria for a City-Forming Object - V. A. Mayboroda; E. A. Shevchenko (Теоретическая и прикладная юриспруденция)
In the article, based on the analysis in the regulation of a historically valuable city-forming object, proposals for further improvement of regulatory regulation are formulated. The authors conclude that city-forming objects are a phenomenon of permanent properties, and therefore it is proposed to differentiate ordinary city-forming objects and historically valuable ones. This approach is based on the fact that urban formation is a process that takes place in modern market conditions and the properties of historical value to such objects begin to be given not by diachronous, but by their synchronous perception in the systemic ratio of the natural and man-made environment.